Mineralogia e geoquímica dos pelitos e carbonatos da formação alcântara, cretáceo superior da bacia de São Luis - Grajaú - AMORIM, Kamilla Borges (2019)
The lower sedimentological succession of the Itapecuru Group is represented by the Alcantara Formation, with several outcrops in the Alcantara region (Maranhão state, northern Brazil). This unit is mainly constituted by mudstones, sandstones and limestones. These litotypes represent a progradacional succession of lagun/washover and tidal channel deposits that overlap huge shoreface deposits. In the last years, sedimentological and stratigraphical studies dealing with the Alcantara Formation were most related to paleoambiental interpretation. The main purpose of this work is to carry out a mineralogical and geochemical characterization of the clay minerals association related to the pelitic rocks of the Alcantara Formation, specially the known palygorskite occurrences. The Limestones were also investigated in order to evaluate their origin and the relationship with the clay minerals. Two geological profiles were sampled and described in the Alcantara city: at the Baronesa beach, and another one at the Livramento Island. Fourteen samples were collected in these two profiles. After laboratory preparation (drying and grinding) samples were submitted to mineralogical and chemical analysis by means of the following techniques: x-ray diffraction (XRD), x-ray fluorescence (XRF), differential thermal analysis (DTA) and thermal gravimetric analysis (DTG), scanning electron microscopy (SEM) and petrography (two samples of limestones). The results showed that the Baronesa Beach profile is mainly composed by sandstones at the base, followed by mudstones and intercalations of limestones. A wide clay mineral assemblage was described in a lagoon environment, with different contents of palygorskite, chlorite, illite, smectite and traces of kaolinite. Small amounts of dolomite, calcite and feldspars were also observed. In the Livramento Island, sandstones deposited by storm-processes are dominant, with minor proportion of mudstones and clearly without associated dolomites. In the Baronesa Beach profile, climatic conditions during the deposition period were arid to semi-arid, with high evaporation, and relatively high salinity and alkaline pH. Two generations of palygorskite were described: white macroscopic accumulations easily observed in the field and frequently described in the literature; and massive accumulation, as the dominant mineral, in the upper muddy levels of the Baronesa Beach profile. This second generation was still not known, and may constitute metric levels with potential economic interest.